2012
DOI: 10.1111/cdev.12022
|View full text |Cite
|
Sign up to set email alerts
|

Differential Associations Between Domains of Sibling Conflict and Adolescent Emotional Adjustment

Abstract: Issues of equality and fairness and invasion of the personal domain, 2 previously identified topic areas of adolescent sibling conflict (N. Campione-Barr & J. G. Smetana, 2010), were examined in 145 dyads (Mfirst-born = 14.97, SD = 1.69 years; Msecond-born = 12.20, SD = 1.90 years) for their differential effects on youths' emotional adjustment over 1 year. The impact of internalizing symptoms on later sibling conflicts also was tested. Invasion of the personal domain conflicts were associated with higher level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 29 publications
3
35
2
Order By: Relevance
“…Also, this study did not account for the direction of effects, and examined sibling relationship quality at only 1 time point. Some literature has found that greater internalizing symptomatology and lower self-esteem predicted increases in sibling conflict over time (Campione-Barr et al 2013), highlighting that the sibling relationship and youth psychological functioning have reciprocal influences. Also, this study focused on risk of parent factors for child outcomes, but studies show these associations to also have bidirectional influence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, this study did not account for the direction of effects, and examined sibling relationship quality at only 1 time point. Some literature has found that greater internalizing symptomatology and lower self-esteem predicted increases in sibling conflict over time (Campione-Barr et al 2013), highlighting that the sibling relationship and youth psychological functioning have reciprocal influences. Also, this study focused on risk of parent factors for child outcomes, but studies show these associations to also have bidirectional influence.…”
Section: Discussionmentioning
confidence: 99%
“…Low warmth and high hostility within the sibling relationship have been associated cross-sectionally with high levels of internalizing problems including anxiety symptoms, depressed mood, and low self-esteem (Campione-Barr et al 2013; Dunn et al 1994a, b; Padilla-Walker et al 2010; Stocker 1994). Self-reported and observed sibling conflict and aggression have been associated with externalizing problems such as antisocial behaviors in youth, whereas sibling relationships characterized by collaboration and affection were not linked with externalizing behaviors (Aguilar et al 2001; Criss and Shaw 2005).…”
Section: Sibling Relationship Quality and Child Outcomesmentioning
confidence: 99%
“…However, Hastings and Taunt (2002) argue positive familial relationships help mitigate caregiver burden, therefore possibly improving TDS outcomes and decreasing caregiver burden. Although not including CWD, several studies examine links between sibling relationship qualities and individual child adjustment (Campione- Barr, Greer, & Kruse, 2013). In addition, Gass and colleagues (2007) report typically developing children with affectionate sibling relationships are less likely to demonstrate negative internalizing behavior after experiencing a stressful life event compared to children without such a relationship.…”
Section: Theoretical Model and Related Studiesmentioning
confidence: 99%
“…In interacting with each other, siblings can reinforce or discourage learned behaviours and skills, with both positive and negative implications (Kramer, 2010;Parke & Buriel, 2006). Sibling interactions can promote prosocial behaviours such as helping each other learn how to share and take-turns (White, Ensor, Marks, Jacobs, & Hughes, 2014), to develop social reasoning (Dunn, 2002), to enhance emotional and cognitive development (Campione-Barr, Greer, & Kruse, 2013;Prime, Pauker, Plamondon, Perlman, & Jenkins, 2014), to safeguard against internalising problems, and to increase levels of self-regulation in adolescence (Padilla-Walker, Harper, & Jensen, 2010). In this way, siblings are developmentally advantageous and provide an important interactional context to helping individuals acquire crucial life skills.…”
Section: Why Study Sibling Relationships?mentioning
confidence: 99%
“…Siblings impact each other's acquisition of interpersonal skills (Downey & Condron, 2004), cognitive development and sensitivity (Azmitia & Hesser, 1993;Prime et al, 2014), emotional development and adjustment (Campione-Barr et al, 2013;Kramer, 2014), social understanding (Dunn, 2002), sharing and prosocial skills (White et al, 2014), socio-cognitive reasoning skills (Slomkowski & Dunn, 1992), delinquent behaviour (Bank et al, 1996;Criss & Shaw, 2005;Patterson, 1986), behaviour problems in adolescence (Dunn et al, 1994), development of mental health and behavioural problems (Buist et al, 2013;Tucker et al, 2013), and protection against the adverse effects of marital discord (Jenkins & Smith, 1990). Such is the pervasiveness of the sibling relationship, the strongest predictor of well-being at age 65 among male Harvard alumni was found to be the quality of their sibling relationships during college (G. E. Vaillant & Vaillant, 1990).…”
Section: Intervention For Sibling Conflictmentioning
confidence: 99%